Integrating Moodle-Based Learning Innovation for Digital Pedagogy - Manurung, Asrar Aspia; Syafrayani, Putri Rizki (Indonesian Journal of Education and Mathematical Science, 2026)
Technological advancement continues to redefine the landscape of education, promoting a transition from traditional instruction to digital pedagogy. One manifestation of this shift is the integration of Moodle as a web-based interactive learning platform. This study explores the innovative integration of Moodle in distance learning through a systematic literature review. Nine scholarly articles were analyzed to identify how Moodle contributes to interactive online learning, the pedagogical benefits it offers, and the barriers that challenge its implementation. Findings indicate that Moodle supports dynamic learning through flexible access, collaboration, and interactive design. However, technical constraints and communication issues may limit satisfaction among users. Educational institutions are encouraged to innovate pedagogically by optimizing Moodle features to create engaging and inclusive digital classrooms.